Analisis Idiomatik dalam Terjemahan Lagu “Anaheim” dan “Paths” Karya Nicole Zefanya - Joylasheva, Jasmine Puspa; Dewi, Ika Sari (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
This study aims to examine the forms and idiomatic meanings in the translated lyrics of the songs “Anaheim” and “Paths” by Nicole Zefanya (NIKI) based on Chitra Fernando’s theory of idioms and Peter Newmark’s translation methods. The idioms found in the lyrics are analyzed using a qualitative descriptive approach to identify pure idioms, semi-idioms, and literal idioms, along with their meanings in emotional and cultural contexts. The results indicate that both songs make significant use of pure idioms. This use reflects the emotional depth and symbolism embedded in the lyrics. The translation methods employed in both songs include communicative, semantic, and literal translation methods. The communicative method is the most frequently applied, as it effectively conveys emotional messages and cultural context. The implications of this research lie in its contribution to applied linguistics and literary translation studies, particularly in understanding idioms as cultural expressions in modern music. This study is also beneficial for the teaching of idiomatic translation to produce more relevant and communicative translations.